Study of Household Endowment and Poverty Reduction - Ijila, O. J.; Sanusi, W. A. (Selected Topics in Humanities and Social Sciences Vol. 8, 2021)
The influence of household endowments (capital and human asset) on the welfare condition of households has not received adequate attention despite its importance. Due to the high incidence of poverty in Sub-Saharan African countries, particularly Nigeria, this study aims to look into the role of household endowments in reducing poverty among rural households in Ijebu-Jesa, Osun State. Data was obtained from 120 households using a multistage sample method and analysed using frequencies and percentages, the Foster Greer and Thorbecke (FGT) index, and logistic regression analysis. The findings indicate that poverty is slightly pervasive among rural households (48.3 %). The determinates of the role of household endowment on poverty reduction considered are age, gender, years of schooling, membership of the cooperative, access to credit, household Income, access to mobile phones, and household size. However, gender (p< 0.030), membership of the cooperative society (p< 0.036), household income (p< 0.009), access to mobile phones (p< 0.037), and household size (p< 0.000) are significant variables for explaining the effect of the household endowment on poverty reduction. It is therefore recommended that the government should introduce programs and policies aimed at facilitating the smooth establishment of cooperative associations in the study area. In addition, tariffs on telecommunication should be subsidised to encourage more individuals to access and utilise mobile phones.